2006
DOI: 10.1002/aqc.761
|View full text |Cite
|
Sign up to set email alerts
|

The impact of introduced signal crayfishPacifastacus leniusculus on stream invertebrate communities

Abstract: ABSTRACT1. The effect of a newly introduced population of signal crayfish (Pacifastacus leniusculus) on a riverine invertebrate community in the River Clyde, Scotland, is examined. Five hypotheses related to crayfish impact on the invertebrate community are tested by comparing sites containing signal crayfish with similar sites in the same river which have not yet been colonized.2. The hypothesis that crayfish significantly reduce the total numbers of invertebrates in the community was supported by this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 7 publications
5
59
1
Order By: Relevance
“…These findings therefore support a growing body of research highlighting the detrimental impact of non-native signal crayfish on fluvial geochemistry, fluvial geomorphology and native aquatic biota (Crawford et al 2006;Johnson et al 2010;Harvey et al 2011). Their large size (typically 10-15 cm in length), aggressive nature, high population densities (up to 20 per square metre) and ability to rapidly colonise new environments have seen signal crayfish populations spread rapidly across Europe putting an increasing number of freshwater environments at risk (Holdich et al 2014;Kouba et al 2014).…”
Section: Significance and Further Researchsupporting
confidence: 73%
“…These findings therefore support a growing body of research highlighting the detrimental impact of non-native signal crayfish on fluvial geochemistry, fluvial geomorphology and native aquatic biota (Crawford et al 2006;Johnson et al 2010;Harvey et al 2011). Their large size (typically 10-15 cm in length), aggressive nature, high population densities (up to 20 per square metre) and ability to rapidly colonise new environments have seen signal crayfish populations spread rapidly across Europe putting an increasing number of freshwater environments at risk (Holdich et al 2014;Kouba et al 2014).…”
Section: Significance and Further Researchsupporting
confidence: 73%
“…Reduced taxa richness has also been documented in a number of other studies following signal crayfish invasion (e.g. Crawford et al 2006;Ruokonen et al 2014;Ercoli et al 2015a, b). When individual species were considered, the most widely cited taxa affected by crayfish invasion were the class of Hirudinea (leeches), which typically demonstrate significant reductions in abundance (Stenroth and Nyström 2003;Crawford et al 2006).…”
Section: Taxa-crayfish Interactionssupporting
confidence: 56%
“…The effect of crayfish presence on invertebrate densities is highly variable with some studies indicating a reduction (Nyström 1999;Crawford et al 2006) whilst others have reported no differences (Lagrue et al 2014;Ercoli et al 2015a). The inconsistent results suggest that any effect on total community abundances is weak and probably a function of original community composition, and highly dependent on individual species responses.…”
Section: Taxa-crayfish Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…High populations and activity of signal crayfish may have negative impacts on resident fish. Signals directly predate on small fish such as stone loach and bullhead (Guan and Wiles, 1997), and on fish fry (Rubin and Svensson, 1993), while alteration of invertebrate communities (Crawford et al, 2006) and cropping of macrophytes by crayfish may put themselves and other denizens at risk (Lodge and Lorman, 1987;Hart, 1993, 1995;Matthews et al, 1993;Nyström and Strand, 1995). Studies have shown that predatory fish interfere with crayfish survival, activity and food consumption, e.g.…”
Section: > Signal Crayfish Pacifastacus Leniusculusmentioning
confidence: 99%